NILAI-NILAI EDUKATIF DALAM BUKU SURGA YANG TAK DIRINDUKAN DAN IMPLIKASINYA DALAM PENDIDIKAN ISLAM - Noor Fatikah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2019)
The relationship between values ??and education is very close. Values ??are involved in every action of education, both in choosing and in deciding everything for the learning needs. Through the perception of values, the teacher can evaluate students. Vice versa, students can measure the level of value presented by the teacher in the learning process. People can also refer to a number of values ??(right-wrong, good-bad, beautiful-not-beautiful) when they consider the educational feasibility experienced by their children. In short, in all forms of human perceptions, attitudes, beliefs and actions in education, values ??are always included. The results of the study found the values ??of Islamic education, and the implications contained in the book heaven that is not missed, namely the Value of Moral Education, including: sincere, patient, grateful, help, honesty, prosperity of the mosque, trying to be a sholehah wife, choosing a good path. The implication is: zuhud, not feeling happy with worldly matters because zuhud believes that what comes from God is the best, Ridho which is: willing, like, happy in accepting the provisions of God, trust that is: one's self-feeling in looking at nature, that what contained in it will not escape from the hands of God and all matters are left to God alone, patience, that is: calm when you get a trial, thankfulness that is: our belief that the blessings that exist are those of God not from others.